25 and 50G optical access network deployment forecasts using bi-logistic curves - Rodrigues, C. (2021)
Different forecast scenarios for the 25G-PON and 50G-PON Globally for both ONT/ONU markets are presented based on modeling by a Bi-Logistic function with reference to GPON existing data.